Microstructural damage based micromechanics model to predict stiffness reduction in damaged unidirectional composites. (June 2018) - Hiremath, Chandrashekhar P; Senthilnathan, K; Naik, Niranjan K; Guha, Anirban; Tewari, Asim
Prediction of the residual stiffness of the carbon fiber reinforced polymer composite, subjected to fatigue loading, can be performed using some of the phenomenological models. However, it is still a challenge to find the stiffness based on the known microstructural damage state (that was developed irrespective of the load history). In this work, two micromechanics-based models were developed to predict reduction in the stiffness of the damaged composite. Fiber crack density and interface debonding was used to define the microstructural damage state of the composite. These models account for the fiber crack density in the form of change in either geometry (equivalent ellipsoid model) or material property of the fiber (reduced stiffness model). The microstructural damage state in the unidirectional carbon fiber reinforced polymer composite, obtained from the on-axis tension–tension fatigue loading, was used to validate the models. The results from reduced fiber stiffness model were compared against experiment and finite element analysis for the given microstructural damage. The stiffness obtained using reduced fiber stiffness model was in good agreement with that obtained from the experiment. However, reduced fiber stiffness model underestimated reduction in stiffness compared to finite element analysis.